ASSESSMENT OF FUNCTIONAL CAPACITY OF THE ELDERLY BELONGING TO THE COVERAGE AREA OF AN ESF-CÁCERES-MT - Kainã Jerônimo Rodrigues; Naudia Silva Dias; Eva Couto Garcia; Danyella Rodrigues de Almeida; Vânia Deluque Aguilar (Revista Gestão & Saúde, 2013)
Aging is a universal biological process and progressive and each passing day the number of elderly grows significantly. Parallel to this fact, increases the prevalence of chronic and disabling diseases that compromise the independence and autonomy of the elderly, reflecting negatively on their quality of life. Objective: To evaluate the functional capacity of the elderly, check morbidities and behavioral aspects of this population. Methods: We applied a questionnaire preset, the scale of Lawton and Katz in 104 elderly who lived in the area covered by the Family Health Strategy, aged more than sixty years. Results: Most of the elderly is independent for all ADL and IADL. Regarding the behavioral aspects that negatively and positively to the health of the elderly (smoking, alcohol consumption and exercise) are not practiced by most of them. Note that the prevalent diseases are hypertension and diabetes. Conclusion: Thus, the professional must be aware of the situational analysis of part of the fastest growing population in Brazil and empower themselves to meet their needs holistically, preventing diseases and promoting health for the independence and autonomy characteristics are expressive and significant this age group.